2014
DOI: 10.11648/j.jfns.20140204.20
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Nigerian Honeys Sourced from Different Floral Locations

Abstract: Comparative studies on the quality of honey obtained from different floral locations in Nigeria were investigated. Parameters such as physical properties, chemical, mineral, microbial contents and antimicrobial activity as well as organoleptic quality were evaluated. The results of the physico-chemical properties show the following range of values for acidity (1.36-1.55%), soluble solids (80.96-82.00%), specific gravity (1.41-1.44) and sweetness index (52.52-62.73). While the proximate values were: moisture (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…(Abdulkhaliq and Swaileh, 2017) investigated potassium and sodium concentrations ranging from 183.86 ppm to 104.66 ppm, which are lower than the previous study. The findings agreed with those of (Agbagwa et al, 2011) and(Joel, 2014), who found potassium dominance in the honey. On the other hand, microelements such as Cobalt, Chromium, Manganese, Molybdenum, Nickel, Lead and Selenium were found in the normal range.…”
Section: Lead (Pb)supporting
confidence: 93%
“…(Abdulkhaliq and Swaileh, 2017) investigated potassium and sodium concentrations ranging from 183.86 ppm to 104.66 ppm, which are lower than the previous study. The findings agreed with those of (Agbagwa et al, 2011) and(Joel, 2014), who found potassium dominance in the honey. On the other hand, microelements such as Cobalt, Chromium, Manganese, Molybdenum, Nickel, Lead and Selenium were found in the normal range.…”
Section: Lead (Pb)supporting
confidence: 93%